200 A randomized, placebo-controlled study of galcanezumab in patients with treatment-resistant migraine: double-blind results from CONQUER. Issue 6 (27th May 2022) - Mulleners, Wim; Kim, ByungKun; Láinez, Miguel; Lanteri-Minet, Michel; Aurora, Sheena; Nichols, Russell; Wang, Shufang; Tockhorn-Heidenreich, Antje; Pain, Andrew
Abstract : Objective: CONQUER assessed galcanezumab efficacy and safety in patients with episodic or chronic migraine who had multiple migraine preventive treatment failures. Methods: In this phase 3, double-blind study, patients (aged 18–75 years) met criteria for migraine, had 4–29 monthly migraine headache days, and 2–4 migraine preventive medication category failures in the past 10 years. Patients were randomized to receive galcanezumab 120mg/month (with 240-mg loading dose; N=232) or placebo (N=230). Primary endpoint: overall mean change from baseline in number of monthly migraine headache days across Months 1–3. Key secondary endpoints: ≥50%, ≥75%, or 100% reduction in monthly migraine headache days and change on Migraine-Specific Quality of Life-Role Function Restrictive domain. Results: Galcanezumab-treated patients averaged 4.1 fewer monthly migraine headache days from a baseline of 13.4 versus placebo patients' average of 1.0 fewer from a baseline of 13.0 (between-group difference 3.1; p<0.0001; 95%CI: -3.9, -2.3; effect size=0.72). Galcanezumab was superior to placebo on all key secondary endpoints and did not differ from placebo in terms of safety. Conclusion: Galcanezumab was superior to placebo in preventive treatment of migraine and was safe and well tolerated in patients with previous failures to standard-of-care preventive treatments. pain_andrew@lilly.com